A historical geography of rare earth elements: From discovery to the atomic age. Issue 3 (August 2015) - Klinger, Julie Michelle
Highlights: Presents a historical geography of rare earth elements from discovery to 1960. Argues that exploration and production have co-evolved with international politics. International rare earth politics are defined by a tension between necessity and danger. The production of geological knowledge about rare earth elements is fundamental to international rare earth politics. Abstract: This article presents a historical geography of rare earth elements from their discovery to the atomic age with a focus on the period between 1880 and 1960 in order to lend greater depth to the growing body of scholarship on the relationship between rare earth elements and global political change. Drawing on archival and field research undertaken in the United States, China, Brazil, and Germany between 2011 and 2014, this article advances the following argument. Rare earth elements, and the production of geological knowledge about them, have entangled with contentious politics since their first industrial applications in the late 19th century. The historical geography of rare earth exploration and extraction is defined by a fundamental tension between the military-industrial necessity of these elements and the hazards associated with their production. This tension played a definitive role in international colonial, Cold War, and atomic politics.